Clinical use of pulse oximetry: Official guidelines from the Thoracic Society of Australia and New Zealand. Issue 1 (20th November 2013) - Pretto, Jeffrey J.; Roebuck, Teanau; Beckert, Lutz; Hamilton, Garun
Abstract Pulse oximetry provides a simple, non‐invasive approximation of arterial oxygenation in a wide variety of clinical settings including emergency and critical‐care medicine, hospital‐based and ambulatory care, perioperative monitoring, inpatient and outpatient settings, and for specific diagnostic applications. Pulse oximetry is of utility in perinatal, paediatric, adult and geriatric populations but may require use of age‐specific sensors in these groups. It plays a role in the monitoring and treatment of respiratory dysfunction by detecting hypoxaemia and is effective in guiding oxygen therapy in both adult and paediatric populations. Pulse oximetry does not provide information about the adequacy of ventilation or about precise arterial oxygenation, particularly when arterial oxygen levels are very high or very low. Arterial blood gas analysis is the gold standard in these settings. Pulse oximetry may be inaccurate as a marker of oxygenation in the presence of dyshaemoglobinaemias such as carbon monoxide poisoning or methaemoglobinaemia where arterial oxygen saturation values will be overestimated. Technical considerations such as sensor position, signal averaging time and data sampling rates may influence clinical interpretation of pulse oximetry readings.